Whole-exome sequencing of patients with juvenile myoclonic epilepsy - E. E. Timechko; O. S. Shilkina; N. V. Oreshkova; V. O. Kobanenko; E. A. Osipova; N. A. Shnayder; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния)
Background. Juvenile myoclonic epilepsy (JME) is the most common type of idiopathic generalized epilepsy with onset in adolescence and adulthood. During medical genetic counseling in probands with JME, aggravated epilepsy-related heredity is often detected. However, specific genetic variants of JME predisposition remain inconclusive. The use of contemporary methods of genetic analysis, particularly whole-exome and whole-genome sequencing, allows to detect, confirm and strengthen an association of any certain pathological phenotype with one or another pathogenic variant in a number of genes.Objective: to analyze the results of whole exome sequencing in patients with JME and seek for JME associations.Material and methods. The study included 7 patients with established JME diagnosis and 1 proband child without clinical signs of epilepsy. Whole exome sequencing was carried out by using MiSeq (Illumina, USA), bioinformatics analysis was performed on the Genomenal platform (Novel Software Systems, Russia).Results. Heterozygous carriage of pathogenic variants in the genes of recessive diseases was revealed: SACS, AHI1, CEP164, ANO10, RMND1, POMGNT1, FLG, ACTB. The analysis of the identified genetic variants in the patients examined showed no association with the clinical picture of the disease. Heterozygous missense mutations in CLCN2, EFHC1, JRK, ME2 genes and frameshift mutation in the CACNB4 gene were detected. Conclusion. In recent years, significant efforts were made to identify genes which predispose to JME. During our study, monogenic and/or polygenic pathogenic variants in patients with JME and a child of proband with JME were not identified. The high genetic heterogeneity of JME can explain numerous unsuccessful attempts to find genes predisposing to JME. Further research is necessary to confirm variants associated with potential JME. Advances in genomic technology can expand our understanding of the genetics of this pathology.